Chinese manufacturing moves to Rwanda: A study of training at C&H Garments - Janet Eom (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2018)
As a small, landlocked country with few natural resources, Rwanda has focused on becoming a knowledge-intensive business and technology hub rather than a labor-intensive manufacturing base. But in 2015, a Chinese garment manufacturing firm, C&H Garments, began operations in Kigali. This paper by Janet Eom finds that the Rwandan government's shift towards creating jobs in the manufacturing sector, and implementation of requirements for training and hiring local workers, have been key to negotiating an agreement with C&H Garments that supports technology transfer to Rwandans. However, the C&H factory has faced obstacles such as cultural and linguistic differences; this paper suggests the exchange of African managers between countries may help. Finally, this study holds significance given that the Rwandan government's desire to boost local manufacturing capacity has been at the center of recent trade tensions between Rwanda and the United States under the African Growth and Opportunity Act (AGOA).
Keywords: 330